2008
DOI: 10.1097/mop.0b013e328305e262
|View full text |Cite
|
Sign up to set email alerts
|

An update on childhood urticaria and angioedema

Abstract: Urticaria is a common condition. Our understanding of distinct urticaria subtypes differentially responsive to targeted therapies continues to increase. Due to the myriad of triggers that may cause urticaria, careful individualized patient assessment is necessary to exclude potential etiologies prior to a diagnosis of idiopathic urticaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
0
22
1
4
Order By: Relevance
“…Podejście dia gnostyczne w stosunku do przyczyn PPS w pediatrii nie powinno się różnić od schematu obowiązującego u dorosłych [71][72][73], z wyjątkiem może niemowląt [74]. Istnieją natomiast różnice pomiędzy dziećmi i dorosłymi w zakresie częstości występowania okreś lonych przyczyn choroby [75].…”
Section: Rozpoznawanie Pokrzywki U Dzieciunclassified
“…Podejście dia gnostyczne w stosunku do przyczyn PPS w pediatrii nie powinno się różnić od schematu obowiązującego u dorosłych [71][72][73], z wyjątkiem może niemowląt [74]. Istnieją natomiast różnice pomiędzy dziećmi i dorosłymi w zakresie częstości występowania okreś lonych przyczyn choroby [75].…”
Section: Rozpoznawanie Pokrzywki U Dzieciunclassified
“…Bailey and Shaker in a review on update on childhood urticaria and angioedema concluded that long-term corticosteroids therapy and other immunomodulating agents such as omalizumab need an understanding of the adjustments between potential risks and expected benefits of the therapy, evaluating possible side effects of therapy against the natural history of underlying disease and consultation for decision making was recommended in cases of severe refractory CIU in which immunomodulators or monoclonal antibody therapy is considered (52).…”
Section: Omalizumab In Children With Chronic Urticariamentioning
confidence: 99%
“…Idiopathic urticaria constitutes approximately 80% of all cases of chronic urticaria (3,11). After idiopathic urticaria physical urticaria is the second most frequently observed urticaria.…”
Section: Classificationmentioning
confidence: 99%